Conflicting Role of Land Office and Forestry Department: A Comparative Discussion Regarding to Forest Offences Prevention in Malaysia - Azizan, Muhammad Uzair; Bing, Tham Sikh; Mohd Raid, Maryanti; Mohammad, Mohammad Tahir Sabit; Hussin, Khadijah; Megat Abd Rahman, Megat Mohd Ghazali; Nadzri, Muhammad Izuan (Jurnal Ilmu Lingkungan, 2017)
This article study the discrepancy between theory and practice, especially the roles play by Land Office and Forestry Department in term of overlapping of power and penalties between Land Office and Forestry Department especially the forest on the state land leading to susceptibility in monitoring and enforcement system. The whole empirical works took place in the Central Region of Peninsular Malaysia namely as Negeri Sembilan. The total area of permanent reserved forest in that state is 155,531 hectares including the Permanent Reserved Forest Johol which was selected as the case study in this research. An exploratory research design was adopted in this research. Therefore, in-depth interviews have been done with officers from the Land Office and Forestry Department regarding their role and powers in monitoring and enforcement system to combat forest offences in Permanent Reserved Forest Johol. While data collected was analyzed using the descriptive analysis method. Content analysis was used to identify the similarities and dissimilarities of acts that empower Land Office and Forestry Department to taking action against forest offences. Theoretically, there are overlapping powers occurs between Land Office and Forestry Department identified in National Land Code 1965 and National Forestry Act 1984 in terms of arrestment of the forest offenders and seized their equipment. However, penalties imposed by both acts are very different. Practically, both authorities have divided their responsibility and power accordingly to avoid overlapping. Issues and challenges that faced by them have been found and most of them are similar. There should be an amendment to the acts in terms of the penalty imposed by both authorities. The penalty stated in both acts should be synchronized or the related sections be removed if the authorities do not implement it practically to avoid overlapping and conflicting of action imposed between two acts.Keywords: state land, forest, forest offences, penalties, monitoring, enforcement, overlapping of powerCitation: Azizan, M.U., Bing, T.S., Raid, M.M., Mohammad, M.T.S, Hussin, K., Rahman, M.M.G.A., and Nadzri, M.I. (2017). Conflicting Role of Land Office and Forestry Department: A Comparative Discussion Regarding to Forest Offences Prevention in Malaysia. Jurnal Ilmu Lingkungan, 15(1), 11-19, doi:10.14710/jil.15.1.11-19